Transparent, simple and robust fast-and-frugal trees and their construction - Martignon, Laura; Erickson, Tim; Viale, Riccardo (Frontiers in Human Dynamics, 2022)
Today diagnostic reasoning may combine typical and specialized medical knowledge, elements of numeracy, some ease with the basics from probability theory and, last but not least, ease in interactions with AI tools. We present a facilitating tool for constructing trees, which lead to transparent, simple and robust classifications and decisions. This tool is inspired by the tenets of Bounded Rationality, or more precisely, by a “face” of Bounded Rationality which has been called Ecological Rationality. We briefly present the tenets of Bounded and of Ecological Rationality which provide the framework for the human-machine interaction this paper is devoted to. The claim is that, because of its simplicity and transparency, the interaction is smooth, transparent and successful.